2022
DOI: 10.1098/rspb.2021.2137
|View full text |Cite
|
Sign up to set email alerts
|

Divergent paths in the evolutionary history of maternally transmitted clam symbionts

Abstract: Vertical transmission of bacterial endosymbionts is accompanied by virtually irreversible gene loss that results in a progressive reduction in genome size. While the evolutionary processes of genome reduction have been well described in some terrestrial symbioses, they are less understood in marine systems where vertical transmission is rarely observed. The association between deep-sea vesicomyid clams and chemosynthetic Gammaproteobacteria is one example of maternally inherited symbioses in the ocean. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 108 publications
2
12
0
Order By: Relevance
“…The two sulfur-oxidizing symbionts, Thioglobus and Thiodubilierella species, appear to be obligate autotrophs as the key enzymes of the TCA cycle, 2-oxoglutarate dehydrogenase and malate dehydrogenase, were not found in the MAG ( Supplementary Figure S8 ). This is in agreement with previous observations of symbiotic and free-living organisms from this clade [10, 78, 79]. Both sulfur-oxidizing symbionts have the genes to gain energy from sulfur compounds using the sulfide: quinone oxidoreductase (Sqr), the Sox sulfur oxidation system (SoxYZXAB) and the reverse dissimilatory sulfite reduction (rDSR) system, which catalyzes the oxidation of sulfide to sulfate via the adenosine-5’-phosphosulfate, using the adenylylsulfate reductase and sulfate adenylyltransferase for the two final steps of the pathway.…”
Section: Resultssupporting
confidence: 94%
“…The two sulfur-oxidizing symbionts, Thioglobus and Thiodubilierella species, appear to be obligate autotrophs as the key enzymes of the TCA cycle, 2-oxoglutarate dehydrogenase and malate dehydrogenase, were not found in the MAG ( Supplementary Figure S8 ). This is in agreement with previous observations of symbiotic and free-living organisms from this clade [10, 78, 79]. Both sulfur-oxidizing symbionts have the genes to gain energy from sulfur compounds using the sulfide: quinone oxidoreductase (Sqr), the Sox sulfur oxidation system (SoxYZXAB) and the reverse dissimilatory sulfite reduction (rDSR) system, which catalyzes the oxidation of sulfide to sulfate via the adenosine-5’-phosphosulfate, using the adenylylsulfate reductase and sulfate adenylyltransferase for the two final steps of the pathway.…”
Section: Resultssupporting
confidence: 94%
“…Also, it is also consistent with the classification of Bathymodioline symbionts (genus Thiodubiliella ) at the phylogenomic relationship (Figure 3) and their symbiotic mode (Halary et al, 2008; Ikuta et al, 2021). Previous studies showed symbionts in Pliocardiinae clams are always detected as intracellular endosymbionts within bacteriocytes (Ip et al, 2021; Newton et al, 2007; Perez et al, 2022). Therefore, we make a hypothesis that Ca .…”
Section: Resultsmentioning
confidence: 96%
“…It is worth noting that symbionts from the Pliocardiinae clams are exclusively found in the genera Ruthia and Vesicomyosocius (Johnson et al, 2017; Ozawa et al, 2017), with congruent relationships between these clams and their symbionts, as indicated by the phylogenies of their mitochondrial and symbiotic genes (Perez et al, 2022). Some incongruent relationships between them might result from occasional ancient horizontal acquisition at the species level (Ozawa et al, 2017) or horizontal recombination within the populations (Russell et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…2; Table S7). Although we cannot fully exclude that the presence of some lowly abundant strains in individual samples might be due to sample cross-contamination during processing or sequencing, analyses of mitochondrial heterogeneity suggested that intra-sample mitochondrial diversity was in general low (0.00–1.32 variants/Kbp) and relatively characteristic of vertically transmitted symbionts and organelles [61, 62]. One mussel individual from ABE exhibited slightly elevated mitochondrial variant densities (3.54 variants/Kbp).…”
Section: Resultsmentioning
confidence: 99%